Integration of prolapsing technique and one-stitch method of ileostomy during laparoscopic low anterior resection for rectal cancer: a retrospective study - Li, Xiangmin; Tian, Min; Chen, Jingbo; Liu, Yulin; Tian, Hu (Frontiers in Surgery, 2023)
Background: Prolapsing technique is a type of natural orifice specimen extraction surgery (NOSES) that can overcome the difficulty of precise transection of the distal rectum and subsequent anastomosis in a narrow pelvic space. Currently, protective ileostomy is widely utilized in low anterior resection for low rectal cancer, which may reduce the severe consequences caused by anastomotic leakage (AL). The study aimed to combine the prolapsing technique with the one-stitch method of ileostomy and evaluate the surgical outcomes. Methods: A retrospective analysis was conducted on patients with low rectal cancer who underwent protective loop ileostomy in laparoscopic low anterior resection from January 2019 to December 2022. The patients were divided into prolapsing technique combined with one-stitch method of ileostomy (PO) group and traditional method (TM) group, and the intraoperative details and early postoperative outcomes of the two groups were measured. Results: 70 patients met inclusion criteria, including 30 patients who underwent PO and 40 patients who underwent traditional procedure. The PO group had a shorter total operative time than the TM group (197.8±43.4 vs 218.3±40.6 min, P = 0.047). The time of intestine function recovery in the PO group was shorter than that in the TM group (24.6±3.8 vs 32.7±5.4 h, P < 0.001). Compared with the TM group, the average VAS score was significantly lower in the PO group (P < 0.001). The incidence of anastomotic leakage in the PO group was signifificantly lower than that in the TM group (P = 0.034). The operative time of loop ileostomy was 2.0±0.6 min in the PO group, which was significantly less than 15.1±2.9 min in the TM group. Skin irritation was observed in 2 patients in the PO group and 10 patients in the TM group, there was significant difference (P = 0.044). Conclusion: This method is safe and feasible, which reduces the technical difficulty and achieves rapid postoperative recovery with few complications.